Predicting the I-Generation's Interest in Giving Alms via Digital Platforms - Saifudin; Hartiningsih, Sepia; Fatimah, Siti (ZISWAF ASFA, 2024)
The potential for the growth of zakat, infaq, and alms in Indonesia is substantial, especially with the rise of various digital charity platforms. This study aims to predict the intention of Generation Z to donate through the BSI mobile banking platform. It examines the impact of perceived utility, perceived ease of use, and attitude on donation intentions. Social influence was previously tested for its effect on perceived usefulness and perceived ease of use. Additionally, this study explores the role of perceived usefulness and attitude in mediating the relationship between perceived ease of use and donation intention. The population for this study consists of Generation Z individuals residing in Salatiga City, with a sample of 106 respondents selected through incidental sampling. The analysis tool used is SmartPLS 3.2.9. The results indicate that the intention to give alms is influenced more by the attitude toward BSI mobile banking than by perceived usefulness or perceived ease of use. Furthermore, attitude is influenced by both perceived usefulness and perceived ease of use, which are shaped by social influence. It was also found that perceived usefulness and attitude strengthen the impact of perceived ease of use on donation intention. This research contributes to the understanding of digital charitable intentions and can serve as a reference for amil agencies to enhance the ZISWAF (Zakat, Infaq, Sedekah, Waqf) intentions among young people in Indonesia.